2021
DOI: 10.3389/fonc.2021.669739
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LINC00673 Promotes the Proliferation of Cervical Cancer Cells

Abstract: ObjectiveTo study the expression of LINC00673 in cervical cancer and cervical intraepithelial neoplasia (CIN) and to explore the role of LINC00673 in the development of cervical cancer.MethodsThe expression of LINC00673 in serum from cervical cancer patients, CIN patients, and healthy participants was detected by RT-qPCR. The function of LINC00673 in cervical cancer cells was analyzed using in vitro and in vivo experiments.ResultsOur results revealed that serum LINC00673 levels were highest in cervical cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Huang et al found that serum levels of LINC00673 were highest in patients with cervical cancer as compared to those in patients with CIN and normal controls 32 . In addition, increased cell proliferation and cell cycle progression were also reported in SiHa and HeLa cervical cancer cell lines, which exhibited LINC00673 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al found that serum levels of LINC00673 were highest in patients with cervical cancer as compared to those in patients with CIN and normal controls 32 . In addition, increased cell proliferation and cell cycle progression were also reported in SiHa and HeLa cervical cancer cell lines, which exhibited LINC00673 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, lncRNA CCAT1 SNP rs67085638 was correlated with the development of gastric cancer ( Olesiński et al, 2021 ), and lncRNA PCAT1 and its SNP rs2632159 were associated with a higher rate of colon cancer, which involves an angiogenesis process ( Yang et al, 2019 ). LINC00673, a member of the lncRNA family, can enhance the development of certain neoplasms because of its chromatin modulation and transcriptional regulation functions ( Lu et al, 2017 ; Qiao et al, 2019 ; Hsieh et al, 2021 ; Huang et al, 2021 ). LINC00673 SNP rs11655237 could alter the development of several cancers, including hepatocellular carcinoma, pancreatic cancer, and oral cancer ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%